Identification and Analyze of Influence Level on Waste Construction Management of Performance. (2015) - Elizar; Wibowo, M. Agung; Koestalam, Pinardi
Abstract: Waste construction management is a process of identifying, analyzing and managing waste on construction project. The type of waste construction can be as material or not material like waste time, waste cost, waste labour, etc. Waste construction is causing inefficient an activity on construction project. Many practitioners and researchers face challenging circumstances in finding an effective way to prevent and minimize wastes by making the best use of resources. Therefore, some factors need to improve waste construction management performance. This paper proposes a new concept that assists project managers to improve the performance level of a project in term of waste construction management practice. This study is based on the identification of the waste construction management influence factors that play an important role in decreasing waste. Open questionnaire surveys and interviews were conducted to collate professional opinions on key issues such as the definition of waste construction. There are some variables to improve performance of waste construction management. The variables are finding based on the literature and interview from practitioner on construction project. As a result of this work, 5 variables and 22 indicators were identified to improve waste construction management of performance. The variables are assets, human resources, knowledge, technology and policy. The result of the study is expectation to provide recommendation of factor to improve construction waste management of performance.